ANALISIS MANAJEMEN FASILITAS GROUND SUPPORT EQUIPMENT DALAM MENDUKUNG KELANCARAN PENERBANGAN DI BANDAR UDARA RAHADI OESMAN KETAPANG - Rozaky, Muhammad; Masyi`ah, Anita (Sekolah Tinggi Teknologi Kedirgantaraan, 2023)
Ground Support Equipment (GSE) facility management is an activity carried out by Ground Handling officers. In its implementation, management activities start from planning, organizing, implementing, to controlling. The use of a GSE facility also requires procedures and rules related to aviation security and safety. The aim of this research is to find out how GSE facility management supports the smooth running of flights at Rahadi Oesman Airport, Ketapang. This research uses a descriptive qualitative method where data collection techniques are carried out by means of interviews, observation and documentation. Interviews were conducted with the Head of KPN Koperhud, Supervisor of PT. ASI (Avia Sejahtera Iskandar), and Operational Ground Handling. Observations were carried out by observing GSE facility management activities at Rahadi Oesman Airport. And documentation is carried out by reviewing documents related to the research object. Data analysis techniques are carried out using reduction, data presentation and drawing conclusions. Data validation was carried out by technical triangulation and source triangulation. The results of the research show that the challenges faced in GSE facility management activities are when changes or adjustments occur, for example, aircraft having system or engine problems, and also bad weather or GSE facilities suddenly experiencing damage, therefore action is needed. fast and precise in making decisions and it is hoped that this management activity will be safer with the Standard Operating Procedures that officers have when carrying out activities in the field, thereby creating effective flight safety at Rahadi Oesman Airport in Ketapang. Keywords: Facilities management, GSE, Ground Handling